ABSTRACT CURRENT SITUATION AND ASSOCIATED FACTORS OF MEDICAL INCIDENT REPORTING AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aims to evaluate the current status of clinical incident reporting and analyze related factors at Nghe An Oncology Hospital.Subjects and methods: Cross-sectional descriptive analysis was conducted on secondary data from 374 adverse event reports recorded between January 2022 and February 2026.Results: The findings indicated that voluntary reporting was predominant, accounting for 98.7%, with nursing staff and technicians being the primary contributors (60.4%). A significant majority of events transpired during regular working hours (94.1%) and were filed within the mandatory 24-hour window (94.4%). Digital avenues were heavily utilized, specifically through the AppSheet platform (50%) and QR codes (49.7%). Regarding severity, near-misses or non-harm incidents comprised 75.1% of the total, and no high-severity events were recorded. The primary trigger was identified as non-compliance or errors during professional technical procedures (56.4%). Statistical correlations were observed between the reporting channels, professional titles, operational departments, and both the timeliness and data quality of the reports.Conclusions: The digitalized medical incident reporting system initially proved effective. Further improvement of the software, staff training and maintenance of a non-punitive reporting culture are needed.
Keywords: Medical incident, incident reporting, patient safety